'Klar bleiben': a school-based alcohol prevention programme for German adolescents—study protocol for a cluster randomised controlled trial. Issue 11 (16th November 2015) - Tomczyk, Samuel; Hanewinkel, Reiner; Isensee, Barbara
Abstract : Introduction: There is a noticeable increase in hazardous alcohol use during adolescence, which is significantly associated with adverse consequences. In Germany, up to 30% of adolescents report regular heavy episodic drinking. However, only a few German prevention programmes target adolescents of legal drinking age (16 years and above); thus, this trial aims to develop, implement and evaluate 'Klar bleiben' ('Stay clearheaded'), a school-based prevention programme for grade 10 students. Methods and analysis: 'Klar bleiben' consists of a class commitment to drink responsibly and refrain from hazardous consumption patterns for 9 weeks. The commitment is accompanied by educational lessons on alcohol-related cognitions and consequences. It will be evaluated in a sample of approximately 3000 students (150 classes) from two German federal states (Schleswig-Holstein and Lower Saxony) via a two-armed cluster randomised controlled trial with baseline and postassessment 6 months apart. The intervention group (75 classes) will participate in 'Klar bleiben', whereas the control group (75 classes) will receive education as usual. 'Klar bleiben' addresses classes, individuals, teachers and parents. It is based on a social norms approach and aims to reduce hazardous drinking and drinking-related consequences in adolescents. Secondary outcomes include general drinking behaviour, use of other substances, alcohol-related cognitions and social factors. Covariates include sociodemographic characteristics, environmental and individual (vulnerability) factors. Ethics and dissemination: 'Klar bleiben' provides a multicomponent school-based programme that bridges a gap in alcohol prevention. Similar class-level and social norms-based prevention programmes have already been proven to be successful for other substances among adolescents. Thus, dissemination to other federal states as well as longer term follow-up testing of the robustness of effects is to be anticipated. The study was approved by the Ethics Committee of the German Psychological Society (RH_0620152), and study findings will be disseminated through peer-reviewed publications and conference contributions. Trial registration number: German Clinical Trials Register: DRKS00009424.